2019
DOI: 10.1371/journal.pntd.0007113
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Mycobacteriophage D29 Lysin B during Mycobacterium ulcerans infection

Abstract: Buruli Ulcer (BU) is a cutaneous disease caused by Mycobacterium ulcerans . The pathogenesis of this disease is closely related to the secretion of the toxin mycolactone that induces extensive destruction of the skin and soft tissues. Currently, there are no effective measures to prevent the disease and, despite availability of antibiotherapy and surgical treatments, these therapeutic options are often associated with severe side effects. Therefore, it is important to develop alternative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…Indeed, mycobacteriophages have not only shown their potential to treat Mycobacterium abscessus infection (Dedrick et al, 2019), but they have also been used for the development of phage-based diagnostics (Jacobs et al, 1993;Pearson et al, 1996;Park et al, 2003). Among the many mycobacteriophages, D29, which is a virulent phage and is capable of infecting and killing both slow and fast growing mycobacterial species (Ford et al, 1998;Rybniker et al, 2006), and its lysis enzymes have been used to kill M. tuberculosis and other mycobacteria in various animal-based experiments (Carrigy et al, 2019;Fraga et al, 2019). The host cell lysis is governed by the protein products of the "Lytic cassette" genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, mycobacteriophages have not only shown their potential to treat Mycobacterium abscessus infection (Dedrick et al, 2019), but they have also been used for the development of phage-based diagnostics (Jacobs et al, 1993;Pearson et al, 1996;Park et al, 2003). Among the many mycobacteriophages, D29, which is a virulent phage and is capable of infecting and killing both slow and fast growing mycobacterial species (Ford et al, 1998;Rybniker et al, 2006), and its lysis enzymes have been used to kill M. tuberculosis and other mycobacteria in various animal-based experiments (Carrigy et al, 2019;Fraga et al, 2019). The host cell lysis is governed by the protein products of the "Lytic cassette" genes.…”
Section: Introductionmentioning
confidence: 99%
“…The host cell lysis is governed by the protein products of the "Lytic cassette" genes. In D29, the lytic cassette comprises gp10 coding for an endolysin LysA that targets the peptidoglycan cell wall and gp12 producing LysB that targets the outer mycolic acid layer of mycobacteria (Payne et al, 2009;Fraga et al, 2019). Additionally, gp11, which is sandwiched between gp10 and gp12, produces holin that perforates the cell membrane of mycobacteria thus allowing for the diffusion of the hydrolytic enzymes to the periplasm and ensuing cell lysis (Catalao et al, 2013;Kamilla and Jain, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…LysB also degrades trehalose dimycolate (TDM), a glycolipid that plays an important role in mycobacterial pathogenesis [ 104 , 105 ] ( Figure 1 B). Recently, the antimicrobial activity of phage D29 LysB against M. ulcerans has been demonstrated in a mouse model, showing synergistic inhibitory effects with other antimycobacterial drugs in vivo and inducing an immune response by increasing the levels of pro-inflammatory cytokines IFN-γ and TNF in the DLN (draining lymph node) [ 106 ]. Besides the lysis as a primary mechanism of mycobacterial death, other authors have suggested the existence of secondary mechanisms, such as the production of superoxide radicals by lysed cells, or the induction of programmed cell death by mycobacteriophages [ 107 ] ( Figure 1 B).…”
Section: Mycobacteriophagesmentioning
confidence: 99%
“…Phage-derived lytic enzymes such as endolysins are being studied as potential antimicrobial agents to combat infections caused by different gram-negative and -positive pathogens [ 34 , 109 ], with progresses made optimizing lysins through bioengineering [ 106 , 110 , 111 ]. Indeed, a recent study describes the novel concept of “innolysins”, an engineering approach that allows customization of endolysins by combining them with phage Receptor Binding Proteins (RBPs) to target specific bacteria [ 112 ].…”
Section: Mycobacteriophagesmentioning
confidence: 99%
“…Endolysins are bacteriophage-encoded peptidoglycan-disrupting enzymes synthesized at the last stage of the phage life cycle in the infected bacteria [83]. One endolysin, lysine B, was found to lyse M. ulcerans infecting the footpad of experimental mice [84].…”
Section: Mycobacteriophage Therapy Of Mycobacterium Tuberculosismentioning
confidence: 99%